2012
DOI: 10.3384/rela.2000-7426.rela0051
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical research

Abstract: This text is about life narratives, memory and time as basic elements in autobiographical research. Aspects of these have seemed important to me whilst I have been conducting and coordinating a research project involving a team of researchers from Brazil and other countries. In this article I take the memory of the individual narrator as the focus, despite the fact that the memories of narrator and researcher are intertwined and co-defined through social and cultural relations and that the narrators´ memory an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…The research paradigm used in this study is qualitative in nature and follows a hermeneutical approach to the subject of research (Dilthey, 2002). Autoethnographical narrations are viewed as related to the hermeneutical perspective of Ricoeur (2007) who emphasises the three dimensionality of narrated time, “looking back to the past with the eyes of the present and allowing prospecting the future” (Barreto Abrahao, 2012, p. 39). The narratives thereby provide a basis for “reflectively and creatively using language” (Lock and Strong, 2010, p. 74).…”
Section: Methodsmentioning
confidence: 99%
“…The research paradigm used in this study is qualitative in nature and follows a hermeneutical approach to the subject of research (Dilthey, 2002). Autoethnographical narrations are viewed as related to the hermeneutical perspective of Ricoeur (2007) who emphasises the three dimensionality of narrated time, “looking back to the past with the eyes of the present and allowing prospecting the future” (Barreto Abrahao, 2012, p. 39). The narratives thereby provide a basis for “reflectively and creatively using language” (Lock and Strong, 2010, p. 74).…”
Section: Methodsmentioning
confidence: 99%
“…This study employs a qualitative research approach, specifically combining autobiographical research and collective narrative study, as demonstrated in the works of Nelson (2003), Pineu (2010), and Abrahão (2012. This type of research was first introduced following Mills' (1959) assertion that "each individual is their own methodology".…”
Section: Research Approachmentioning
confidence: 99%
“…This type of research was first introduced following Mills' (1959) assertion that "each individual is their own methodology". It gained more traction with the establishment of the Self Study Special Interest Group (SIG) in 1992 and has continued to progress since then (Abrahão, 2012;Nelson, 2003). While there may be (Bullough Jr & Pinnegar, 2001;Pinnegar & Daynes, 2007).…”
Section: Research Approachmentioning
confidence: 99%
“…In this conversation with Smith's ideas, I offer stories of how she guided me in developing deeper understandings of my lived experiences as a feminist activist and academic. Memory figures prominently (Barreto-Abrahão, 2010); in this sense, my stories are meaning-making accounts of certain aspects of my life, not an empirical rendering. In some sections I begin with a haiku, a short-form poem consisting of three lines.…”
Section: Mots-clés Mémoire Réflexive éPistémologie Féministe Relation...mentioning
confidence: 99%